2021
DOI: 10.1073/pnas.2019617118
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of the Italian exit strategy from COVID-19 lockdown

Abstract: After the national lockdown imposed on March 11, 2020, the Italian government has gradually resumed the suspended economic and social activities since May 4, while maintaining the closure of schools until September 14. We use a model of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission to estimate the health impact of different exit strategies. The strategy adopted in Italy kept the reproduction number Rt at values close to one until the end of September, with marginal regional differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 33 publications
1
81
3
Order By: Relevance
“…Moreover, since social support has been demonstrated to bolster coping abilities and to positively influence the resilience of healthcare workers during the pandemic, we can hypothesize that the sense of gratitude conveyed by both media and society during the first phases of the COVID-19 outbreak may have been helpful in determining a sense of effectiveness in the healthcare teams [34]. However, given the notable changes that pandemic control measures have over time [35], coupled with the ambiguity inherent in some media-conveyed messages [36], further and longitudinal evaluations of the influence of social support on coping abilities of HCWs are needed. The observation that physicians have shown superior coping skills compared to nurses and other health professionals confirms that HCWs should not be considered a homogeneous population in the psychological impact they have as a result of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, since social support has been demonstrated to bolster coping abilities and to positively influence the resilience of healthcare workers during the pandemic, we can hypothesize that the sense of gratitude conveyed by both media and society during the first phases of the COVID-19 outbreak may have been helpful in determining a sense of effectiveness in the healthcare teams [34]. However, given the notable changes that pandemic control measures have over time [35], coupled with the ambiguity inherent in some media-conveyed messages [36], further and longitudinal evaluations of the influence of social support on coping abilities of HCWs are needed. The observation that physicians have shown superior coping skills compared to nurses and other health professionals confirms that HCWs should not be considered a homogeneous population in the psychological impact they have as a result of the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…that is the same condition as (36) providing the stability of the endemic equilibrium (as well as the instability of the disease-free equilibrium). On the other hand, when R i < 1 the epidemics reduces and tends to vanish.…”
Section: Denoting By Z I (T) = (E I (T) I U I (T) I D I (T))mentioning
confidence: 88%
“…At the same time, being ( 30) not satisfied, the epidemicfree equilibrium is unstable. The opposite situation arises when (36), and then (21), are not satisfied: the only admissible equilibrium point is the epidemic-free one, and it is locally asymptotically stable.…”
Section: Equilibria and Stability Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…These findings confirmed results from a modelling study in eleven European countries showing how Rt began to drop after school closure and other NPIs, even before complete national lockdown ( Flaxman et al, 2020 ). In Vietnam, after social distancing was lifted in Period 4, a peak of Rt was observed, which eventually led to the biggest outbreak in Period 5, which can be explained through the reintroduction of imported cases into high-risk areas ( Yeoh et al, 2021 ), and/or the resumption of previous social mixing patterns as observed in several countries following lockdowns ( SantamarĂ­a and Hortal, 2021 , Marziano et al, 2021 ). In Period 5, a wide-scale lockdown of two affected cities (Da Nang and Hai Duong), coupled with extensive testing and quarantine policies (see Supplement 1 ), resulted in a substantial reduction of Rt after only two weeks, and in the containment of outbreaks two months later.…”
Section: Discussionmentioning
confidence: 99%